The Significance of Feed-Borne Mycotoxins in Aquaculture - Smith, Trevor K. (Avances en Nutrición Acuicola, 2008)
Mycotoxins are fungal metabolites which can reduce growth and adversely alter metabolism of aquaculture species. The pathological states arising from the consumption of feeds contaminated with mycotoxins are mycotoxicoses. Mycotoxins can be formed in the field preharvest and may continue to be formed under suboptimal storage conditions postharvest. Some fungi, such as Aspergillus flavus, are usually found in areas with tropical and semitropical climates. This mold produces the carcinogenic hepatotoxin, aflatoxin. Numerous studies have shown aquaculture species to be particularly susceptible to aflatoxicosis. Fusarium fungi, however, are more common in temperate climates and Fusarium mycotoxins are likely the most common mycotoxins on a global basis. The Fusarium mycotoxins are not typically carcinogenic but aquaculture species have been shown to be sensitive to the presence of feed-borne Fusarium mycotoxins.